Survival following liver transplantation for liver-only colorectal metastases compared with hepatocellular carcinoma. Issue 6 (13th March 2018) - Dueland, S; Foss, A; Solheim, J M; Hagness, M; Line, P-D
Abstract: Background: Liver transplantation is considered the standard of care for patients with hepatocellular carcinoma (HCC) within the Milan criteria. Liver transplantation in patients with unresectable colorectal cancer with liver-only disease has been shown to be associated with a 5-year overall survival rate of 56 per cent, compared with 9 per cent in patients receiving standard palliative chemotherapy. The aim of the present study was to compare disease-free (DFS) and overall (OS) survival after liver transplantation in patients with HCC and those with colorectal metastases. Methods: Data were collected from the SEcondary CAncer (SECA) study database and an institutional (national) database of patients undergoing liver transplantation for HCC; all liver-transplanted patients were included. Patients with colorectal metastases treated by liver transplantation were divided into high- and low-risk groups for mortality based on carcinoembryonic antigen levels, response to chemotherapy, largest lesion at time of transplantation and time from primary surgery to transplantation. Results: Patients with colorectal metastases had a median of 8 lesions, compared with 1 in patients with HCC within the Milan criteria. DFS was shorter in both the high-risk and the low-risk colorectal cancer groups compared with that in patients with HCC. The 5-year OS rate in the low-risk colorectal cancer group was 75 per cent, compared with 76 per cent in patients with HCC within the Milan criteria. The 5-year OS rate in patients with HCC beyond the Milan criteria was 56 per cent. Conclusion: The low-risk group of patients with colorectal cancer and unresectable liver-only disease had a 5-year OS rate following liver transplantation similar to that of patients with HCC with lesions within the Milan criteria. Abstract : Valid treatment option